Crop root system architecture in drought response - Zhang, Yanjun; Wu, Xi; Wang, Xingrong; Dai, Mingqiu; Peng, Yunling (Journal of genetics and genomics, 2025)
Drought is a natural disaster that profoundly impacts on global agricultural production, significantly reduces crop yields, and thereby poses a severe threat to worldwide food security. Addressing the challenge of effectively improving crop drought resistance (DR) to mitigate yield loss under drought conditions is a global issue. An optimal root system architecture (RSA) plays a pivotal role in enhancing the capacity of crops to efficiently uptake water and nutrients, which consequently strengthens their resilience against environmental stresses. In this review, we discuss the compositions and roles of crop RSA and summarize the most recent developments in augmenting drought tolerance in crops by manipulating RSA-related genes. Based on the current research, we propose the potential optimal RSA configuration that could be helpful in enhancing crop DR. Lastly, we discuss the existing challenges and future directions for breeding crops with enhanced DR capabilities through genetic improvements targeting RSA.